New‐generation drug‐eluting stents reduce stent thrombosis and myocardial infarction: A propensity‐score‐adjusted analysis from the multicenter REAL registry (REgistro Regionale AngiopLastiche Dell'Emilia‐Romagna). Issue 5 (14th October 2014) - Vignali, Luigi; Saia, Francesco; Belotti, Laura Maria Beatrice; Solinas, Emilia; Guastaroba, Paolo; Rubboli, Andrea; Manari, Antonio; Mehran, Roxana; Ardissino, Diego; De Palma, Rossana
Abstract : Objectives: The aim of this study was to compare long‐term clinical outcomes in patients treated with new‐generation drug‐eluting stent (DES) or early‐generation DES in a real‐world registry. Background: New‐generation DESs have proved to be more effective and safer than early‐generation DES in randomized trials. However, the effects of new‐generation DES versus early‐generation DES in everyday clinical practice deserve further verification. Methods: A propensity‐score and inverse‐probability weighted analysis of 5, 332 patients undergoing DES implantation (2, 557 new‐generation and 2, 775 early‐generation) between January 1, 2007 and June 30, 2011 was performed, with a median follow‐up of 3 years. We assessed the incidence of major adverse cardiovascular events (MACE: all‐cause death, nonfatal myocardial infarction [MI], and target vessel revascularization [TVR]), and angiographic stent thrombosis (ST) during follow‐up. Results: At 3‐years, new‐generation DES in comparison with early‐generation DES were associated with a reduced risk of MI (5% versus 7.4%, hazard ratio [HR] = 0.65, 95% confidence interval [CI] = 0.51–0.82, P = 0.0004) and angiographic ST (0.5% vs. 1.1%, HR = 0.35, 95% CI 0.17–0.72, P = 0.004), whereas, the risk of TVR (10.9% vs. 13.5%; HR 0.99, 95% CI 0.84–1.16, P = 0.99) and overall MACE was not significantly different (19.2% vs. 22.4%, HR = 0.94, 95% CI = 0.83–1.07, P = 0.35). Conclusions: Our data from a large all‐comers multicenter registry confirm that, in comparison with early‐generation DES, the use of new‐generation DES is associated with similar efficacy and increased long‐term safety, because of a reduced risk of ST and MI. © 2014 Wiley Periodicals, Inc.